Development and Validation of an Ultrasensitive Procalcitonin Sandwich Immunoassay - Carcamo Yañez, Viviana; Göpfert, Jens; Otto, Markus; Tumani, Hayrettin; Peter, Andreas; Joos, Thomas (High-throughput, 2017)
Procalcitonin (PCT) is well established as a highly specific biomarker for the detection of bacterial infections and sepsis. However, the currently available diagnostic tests are not able to detect very low or very early increases of PCT or even baseline levels in healthy individuals or patients with non-bacterial infections. In order to be able to detect these very low concentrations of PCT, a sandwich immunoassay was developed using high sensitivity Single Molecule Array technology (Simoa). The assay was thoroughly validated and applied to analyze human cerebrospinal fluid (CSF) and serum samples from patients with bacterial or viral meningitis as well as CSF, serum, and K2 EDTA plasma from healthy control subjects. A 50-fold increase in sensitivity compared to the current gold standard assays was achieved, which was sensitive enough for the detection of baseline PCT levels. Both serum and CSF showed significantly elevated PCT levels in patients with bacterial meningitis compared to patients with viral meningitis and the healthy control group. Procalcitonin concentration levels for patients with viral meningitis and the control group could be measured, but were not significantly different. The determination of PCT in the low pg·mL−1 range could help to improve the monitoring of bacterial infectious diseases, as PCT level changes could be detected earlier.